Etiology and perinatal outcome of periviable fetal growth restriction associated with structural or genetic anomaly. (14th February 2020) - Dall'Asta, A.; Girardelli, S.; Usman, S.; Lawin‐O'Brien, A.; Paramasivam, G.; Frusca, T.; Lees, C. C.
ABSTRACT: Objective: To investigate the etiology and perinatal outcome of periviable fetal growth restriction (FGR) associated with a structural defect or genetic anomaly. Methods: This was a retrospective study of singleton pregnancies seen at a referral fetal medicine unit between 2005 and 2018, in which FGR (defined as fetal abdominal circumference ≤ 3 rd percentile for gestational age) was diagnosed between 22 + 0 and 25 + 6 weeks of gestation. The study group included pregnancies with periviable FGR associated with a genetic or structural anomaly (anomalous FGR), while the control group consisted of structurally and genetically normal pregnancies with periviable FGR (non‐anomalous FGR). Results of genetic testing, TORCH screen and postmortem examination, as well as perinatal outcome, were investigated. Results: Of 255 pregnancies complicated by periviable FGR, 188 were eligible; of which 52 (28%) had anomalous FGR and 136 (72%) had non‐anomalous FGR. A confirmed genetic abnormality accounted for 17/52 cases (33%) of anomalous FGR, with trisomy 18 constituting over 50% (9/17; 53%). The most common structural defects associated with FGR were central nervous system abnormalities (13/35; 37%). Overall, 12 (23%) cases of anomalous FGR survived the neonatal period. No differences were found in terms of perinatal survival between pregnancies with anomalous and those with non‐anomalous FGR. Conclusions: Most pregnancies complicated by anomalous FGR were associated with a structural defect. The presence of an associated genetic defect was invariably lethal, while those with a structural defect, in the absence of a confirmed genetic abnormality, survived into infancy in over 90% of cases, with an overall one in three chance of perinatal survival. These data can be used for counseling prospective parents. Copyright © 2019 ISUOG. Published by John Wiley & Sons Ltd.